The physiology of long-distance migration: extending the limits of endurance metabolism - Weber, J. M. (The Journal of Experimental Biology, 2009)
Long-distance migrants have evolved specific adaptations that make their athletic records possible. Unique mechanisms explaining their amazing capacity for endurance exercise have now been uncovered, particularly with respect to energy storage, mobilization, transport and utilization. Birds are champions of migration because flying offers a key compromise: it allows more rapid movement than swimming, but has a lower cost of transport than running. High efficiency for muscle contraction, pointed wings, low wingloading, travelling in V-formations, storing fuel as energy-dense lipids and atrophy of non-essential organs are some of their strategies to decrease the cost of transport. The ability to process lipids rapidly also emerges as a crucial component of the migrant phenotype. High lipid fluxes are made possible by lipoprotein shuttles and fatty acid binding proteins (FABPs) that accelerate lipid transport and by upgrading the metabolic machinery for lipolysis and lipid oxidation. Preparation for long flights can include natural doping on n-3 polyunsaturated fatty acids (n-3 PUFAs) from unique invertebrate diets. Muscle performance is improved by restructuring membrane phospholipids and by activating key genes of lipid metabolism through peroxisome proliferator-activated receptors (PPARs). The physiological secret to long migrations does not depend on a single .magic' adaptation but on the integration of multiple adjustments in morphology, biomechanics, behavior, nutrition and metabolism. Research on the physiology of migrants improves the fundamental knowledge of exercise biology, but it also has important implications for wildlife conservation, treating obesity and improving the performance of human athletes.